Quali oggetti di studio e quali prospettive di ricerca per la pedagogia nel tempo delle transizioni umane e digitali? - Maria Luisa Iavarone (Studi sulla Formazione)
The pandemic crisis period we have been going through has made it abundantly clear that the training system needs to be strengthened in terms of life skills. The aim of this paper is to demonstrate the importance of strengthening individuals’ life skills, which in the digital-human ecosystem in which we are immersed are increasingly digital soft skills. This awareness requires the promotion of Digital Wellbeing as an educational territory that has not yet been responsibly presided over.